SARS-CoV-2 pandemic and research gaps: Understanding SARS-CoV-2 interaction with the ACE2 receptor and implications for therapy - Datta, Prasun K. (Theranostics, 2020)
The COVID-19 pandemic is an emerging threat to global public health. While our current understanding of COVID-19 pathogenesis is limited, a better understanding will help us develop efficacious treatment and prevention strategies for COVID-19. One potential therapeutic target is angiotensin converting enzyme 2 (ACE2). ACE2 primarily catalyzes the conversion of angiotensin I (Ang I) to a nonapeptide angiotensin or the conversion of angiotensin II (Ang II) to angiotensin 1-7 (Ang 1-7) and has direct effects on cardiac function and multiple organs via counter-regulation of the renin-angiotensin system (RAS). Significant to COVID-19, ACE2 is postulated to serve as a major entry receptor for SARS-CoV-2 in human cells, as it does for SARS-CoV. Many infected individuals develop COVID-19 with fever, cough, and shortness of breath that can progress to pneumonia. Disease progression promotes the activation of immune cells, platelets, and coagulation pathways that can lead to multiple organ failure and death. ACE2 is expressed by epithelial cells of the lungs at high level, a major target of the disease, as seen in post-mortem lung tissue of patients who died with COVID-19, which reveals diffuse alveolar damage with cellular fibromyxoid exudates bilaterally. Comparatively, ACE2 is expressed at low level by vascular endothelial cells of the heart and kidney but may also be targeted by the virus in severe COVID-19 cases. Interestingly, SARS-CoV-2 infection downregulates ACE2 expression, which may also play a critical pathogenic role in COVID-19. Importantly, targeting ACE2/Ang 1-7 axis and blocking ACE2 interaction with the S protein of SARS-CoV-2 to curtail SARS-CoV-2 infection are becoming very attractive therapeutics potential for treatment and prevention of COVID-19. Here, we will discuss the following subtopics: 1) ACE2 as a receptor of SARS-CoV-2; 2) clinical and pathological features of COVID-19; 3) role of ACE2 in the infection and pathogenesis of SARS; 4) potential pathogenic role of ACE2 in COVID-19; 5) animal models for pathological studies and therapeutics; and 6) therapeutics development for COVID-19.